Langit dan Bumi yang Baru: Eskatologi berdasarkan Teologi Biblika tentang Tempat Kediaman Allah - Yohanes, Hendra (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2020)
Abstract Popular Christian eschatology tends to nullify the earth from the biblical image of the new heaven and earth. On the contrary, the biblical eschatology shows that the new heaven and earth will be the dwelling place of God who will ultimately be with the redeemed people. Using the method of intertextual exegesis, this study constructs a biblical eschatology in terms of the theme of the dwelling place of God that frames the biblical portraits of Eden in the first creation and the New Jerusalem in the new heaven and earth. Sinful humankind has been expelled from Eden, the first sanctuary, yet the New Jerusalem will be the holy dwelling place of God, where God’s people enjoying eternal life. The new heaven and new earth is the telos of God’s salvation plan where no sin defiles the cosmic temple anymore. The biblical eschatological hope promises God’s people about living as the royal priests on the earth that God will renew at the eschaton. Abstrak Eskatologi Kristen populer cenderung mengecualikan bumi dari gambaran alkitabiah langit dan bumi yang baru. Sebaliknya, eskatologi biblika menunjukkan bahwa langit dan bumi yang baru merupakan tempat kediaman Allah yang akhirnya akan bersama dengan umat tebusan-Nya. Penulis menggunakan metode eksegesis intertekstual untuk mengonstruksi eskatologi biblika berdasarkan tema tempat kediaman Allah yang membingkai gambaran-gambaran Alkitab, yakni Eden di dunia ciptaan yang pertama dan Yerusalem Baru di langit dan bumi yang baru. Manusia yang berdosa telah diusir dari Eden, tempat kudus yang pertama. Namun Yerusalem Baru merupakan tempat kediaman Allah yang kudus, di mana umat Allah akan menikmati kehidupan kekal. Langit dan bumi yang baru merupakan tujuan rencana keselamatan Allah, di mana tiada lagi dosa yang menajiskan bait semesta. Pengharapan eskatologis yang alkitabiah menjanjikan kehidupan umat Tuhan sebagai imamat rajawi di bumi yang akan dibarui oleh Allah pada eschaton.